T字杖歩行で右立脚中期から右立脚終期において右股関節の過外転による右側方への不安定さを認めたくも膜下出血後左片麻痺の症例 - 鈴木, 俊明; 和田, 平悟 (関西理学療法, 2021)
We report a case of left-side hemiplegia due to subarachnoid hemorrhage. When our patient walked with a T-shaped cane, almost no extension and adduction of the left hip joint from the left loading response to the left mid-stance, poor weight transfer to the left lower limb, and instability from the right mid-stance to the right terminal stance due to hyperabduction of the right hip joint were noted. The patient's right hip joint was externally rotated, and the pelvis was left rotated throughout both standing and walking due to internal rotation weakness of the right hip joint. The left hip joint was poorly flexed in the left swing phase due to hypotonia of the left iliacus muscle, and the left lower leg had been swinging out for many years due to left pelvic elevation along with left lumbar flexion. It was necessary to first address the problems of the right lower limb. Left hip extension, adduction, and internal rotation, left ankle dorsiflexion, and left foot supination were absent. In addition, horizontal movement of the pelvis was difficult. An approach improving the left rotation of the pelvis and external rotation of the left lower leg via external rotation of the right hip joint, resulted in extension and adduction of the left hip joint occurring in the middle stage of the left stance, enabling the patient to transfer weight onto the left lower limb.